Readings from classical rhetoric - Matsen, Patricia P., 1933-; Rollinson, Philip B.; Sousa, Marion, 1941 September 11- (Southern Illinois University Press, 1990)
"Here, for the first time in one volume, are all the extant writings focusing on rhetoric that were composed before the fall of Rome. This unique anthology of primary texts in classical rhetoric contains the work of 24 ancient writers from Homer through St. Augustine, including Herodotus, Thucydides, Plato, Aristotle, Cicero, Quintilian, Tacitus, and Longinus. Along with many widely recognized translations, special features include the first English translations of works by Theon and Nicolaus, as well as new translations of two works by important sophists, Gorgias' encomium on Helen and Alcidamas' essay on composition. The writers are grouped chronologically into historical periods, allowing the reader to understand the scope and significance of rhetoric in antiquity. Introductions are included to each period, as well as to each writer, with writers' biographies, major works, and salient features of excerpts"--Amazon.com